PERSEPSI MASYARAKAT TERHADAP AGRIBISNIS SAYURAN METODE HIDROPONIK STARTERKIT WICK DI KOTA KENDARI - Asriani Asriani; Wa Embe; Fitria Nafu; Dhian Herdhiansyah (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Consumption of vegetables in the community continues to increase along with the increase in population. Hydroponics is an innovation in agriculture that was developed to increase vegetable production in order to support national food security. This study aims to determine public perception on the Starterkit Wick Hydroponic method of vegetable plants. The location of the study was conducted in Wawowanggu District, Kendari City. Sampling was done by purposive sampling technique. The method used in this research is a descriptive qualitative analysis method with a Likert Scale which is used to measure attitudes, opinions and people's perceptions of the Starterkit Wick Hydroponics method of vegetable plants. Based on the research results obtained by community perceptions of the Starterkit Wick Hydroponics program for vegetable crops based on factors such as narrow land use, good quality, free of pests and diseases, practical, many nutrients, rapid plant growth, suitable for urban areas and as agro-tourism. In general and overall public perceptions of the hydroponic method for starterkit wick systems are at an average value of 3.58 with a high category